Polymorphisms of MMP9 and TIMP2 in Patients with Varicose Veins - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2015)
Background: Genetic predisposition is a suggested risk factor in the etiology of varicose veins. The matrix metalloproteinase (MMP) family degrades extracellular matrix (ECM) and may lead to disturbances in vein wall structure. The activity of MMPs in the ECM are controlled by specific tissue inhibitors of MMPs (TIMP). The present study aimed to investigate the relationship between MMP9 and TIMP2 gene polymorphisms and varicose vein risk. Materials and Methods: Genotyping of the polymorphisms of MMP9 (1562 C/T) and TIMP2 (418G/C) was performed using polymerase chain reaction and restriction-fragment length polymorphism assays in a group of patients with varicose veins (n=63) and healthy controls (n=70). Results: The frequencies of MMP9 alleles and genotypes did not differ significantly between patient and control groups. However, TIMP2 -418 C allele was associated with increased risk for varicose vein formation (p=0.007). It was also shown that the frequency of the GG genotype was significantly higher in the control group than in the patient group (odds ratio=0.333, 95% confidence interval=0.14-0.78, p=0.012). Conclusion: TIMP2-418 C allele is associated with susceptibility for varicose vein formation and individuals with GG genotype may have a lower risk for varicose vein formation.
Keywords: Varicose vein; venous insufficiency; matrix metalloproteinase-9; tissue inhibitor of matrix metalloproteinase-2; gene polymorphism; CHRONIC VENOUS INSUFFICIENCY; MATRIX METALLOPROTEINASES; TISSUE INHIBITOR; GENE POLYMORPHISMS; RISK-FACTORS; DISEASE; CHINESE; EPIDEMIOLOGY